RELEVANCE OF MUI FATWA NO. 24 OF 2017 CONCERNING GUIDELINES FOR BERMUAMALAH IN REGULATING BUZZER ACTIVITIES IN THE DIGITAL ERA - Azka, Ibnu; Widyasari S, Citra (The Ministry of Religious Affairs, The Republic of Indonesia, 2025)
This article aims to discuss the relevance of MUI fatwa no. 24 of 2017 in relation to Buzzer activity in the digital era. In recent years, there has been a functional transformation of Buzzers on social media which connotes the interests of certain individuals which makes this activity negatively oriented. Buzzers are then driven by the interests of social conflicts, political disputes, power relations, and so on. Meanwhile, there is no fatwa that specifically regulates guidelines for Buzzer activities, but in 2017 the MUI issued a fatwa regarding guidelines for muamalah via social media. Therefore, this article will examine the relevance of MUI fatwa no. 24 of 2017 concerning guidelines for muamalah via social media with the current phenomenon of Buzzer activity. This research uses Netnography research with a content analysis approach. The results of the research show that through purposive analysis, it can be seen that the MUI fatwa and Buzzer activity guidelines have similar goals, namely creating a digital environment that is clean and free from negative content. However, the approaches they use to achieve these goals are different. The MUI Fatwa emphasizes moral and religious values, while the Buzzer Activity Guidelines focus more on legal aspects and social norms. Although the approaches are different, they complement and strengthen each other. The relevance between the MUI Fatwa and the Buzzer Activity Guidelines can be seen in the objectives, principles, obligations and prohibitions.